2004
DOI: 10.1021/jm034197s
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Fluoroindolocarbazole Series as Selective Topoisomerase I Active Agents. Discovery of Water-Soluble 3,9-Difluoro-12,13-dihydro-13-[6-amino-β- d-glucopyranosyl]-5H,13H-benzo[b]- thienyl[2,3-a]pyrrolo[3,4-c]carbazole- 5,7(6H)-dione (BMS-251873) with Curative Antitumor Activity against Prostate Carcinoma Xenograft Tumor Model

Abstract: A series of fluoroindolocarbazoles were studied with respect to their topoisomerase I activity, cytotoxicity, selectivity, and in vivo antitumor activity. Emerging from this series was BMS-251873, a potential clinical candidate possessing a robust pharmacological profile including curative antitumor activity against prostate carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…[1][2][3][4] The mechanisms of antitumor effects of carbohydrate derivatives of indolocarbazoles include DNA damage and inhibition of the enzymes critical for cell viability, namely, topoisomerase I (topo I) and serine/threonine protein kinases, that is, cyclin dependent kinases (CDKs) and the checkpoint kinase ChK1. [1,[5][6][7][8][9] Rebeccamycin and its analogues with N-glycoside bonds can stabilize topo I-mediated DNA single strand breaks. [4][5][6][7][10][11][12][13] The crystal structure of the complex of rebeccamycin analogue SA315F with duplex DNA and topo I revealed that SA315F intercalates into the site of a DNA break, whereas the sugar residue interacted with the enzyme in the DNA major groove.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The mechanisms of antitumor effects of carbohydrate derivatives of indolocarbazoles include DNA damage and inhibition of the enzymes critical for cell viability, namely, topoisomerase I (topo I) and serine/threonine protein kinases, that is, cyclin dependent kinases (CDKs) and the checkpoint kinase ChK1. [1,[5][6][7][8][9] Rebeccamycin and its analogues with N-glycoside bonds can stabilize topo I-mediated DNA single strand breaks. [4][5][6][7][10][11][12][13] The crystal structure of the complex of rebeccamycin analogue SA315F with duplex DNA and topo I revealed that SA315F intercalates into the site of a DNA break, whereas the sugar residue interacted with the enzyme in the DNA major groove.…”
Section: Introductionmentioning
confidence: 99%
“…[1,[5][6][7][8][9] Rebeccamycin and its analogues with N-glycoside bonds can stabilize topo I-mediated DNA single strand breaks. [4][5][6][7][10][11][12][13] The crystal structure of the complex of rebeccamycin analogue SA315F with duplex DNA and topo I revealed that SA315F intercalates into the site of a DNA break, whereas the sugar residue interacted with the enzyme in the DNA major groove. [7] Furthermore, in the sugar derivatives of indolocarbazoles that inhibit protein kinase C and CDKs, as well as in staurosporine, the carbohydrate residues are linked to two N atoms of indole.…”
Section: Introductionmentioning
confidence: 99%
“…Fused carbazole derivatives have attracted much attention because they are privileged scaffolds in numerous naturally occurring alkaloids, bioactive organic molecules, and novel organic electroluminescent materials . As a result, a number of synthetic routes toward fused carbazole derivatives have been documented .…”
mentioning
confidence: 99%
“…For example, compound BMS-251873 was reported to be a selective topoisomerase I active agent that showed curative antitumor activity against prostate carcinoma xenografts (Figure ). 11-Arylbenzo­[ b ]­naphtho­[2,3- d ]­thiophene was reported to be a selective PTPase inhibitor that functions as an oral antidiabetic agent . Notably, the use of ladder-type small molecule 2,7-dioctyl­[1]­benzo­thieno­[3,2- b ]­[1]­benzo­thiophene (C8-BTBT) as an organic semiconductor has yielded thin-film transistors with average carrier mobilities as high as 16.4 cm 2 V –1 s –1 .…”
mentioning
confidence: 99%